2018
DOI: 10.1080/21505594.2018.1482179
|View full text |Cite
|
Sign up to set email alerts
|

The cholinergic anti-inflammatory pathway ameliorates acute viral myocarditis in mice by regulating CD4+ T cell differentiation

Abstract: Many studies have found that abnormalities in the proportion and differentiation of CD4+ T cells (Th cells) are closely related to the pathogenesis of viral myocarditis (VMC). Our previous research indicates that the cholinergic anti-inflammatory pathway (CAP) attenuates the inflammatory response of VMC and downregulates the expression of cytokines in Th1 and Th17 cells. This suggests that the cholinergic anti-inflammatory pathway likely attenuates the inflammatory response in VMC by altering Th cell different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…Vagus nerve stimulation has been at the forefront of inflammatory disease research, and there have been many promising results [19][20][21]. Many studies have reported that the vagus nerve regulates the immune response effectively, a concept known as the cholinergic anti-inflammatory pathway [22][23][24][25]. The protective effect of vagus nerve signaling on IR injury in different organs of animals, including the myocardium and brain, has been reported [12,[26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Vagus nerve stimulation has been at the forefront of inflammatory disease research, and there have been many promising results [19][20][21]. Many studies have reported that the vagus nerve regulates the immune response effectively, a concept known as the cholinergic anti-inflammatory pathway [22][23][24][25]. The protective effect of vagus nerve signaling on IR injury in different organs of animals, including the myocardium and brain, has been reported [12,[26][27].…”
Section: Discussionmentioning
confidence: 99%
“…And α 7nAChR is a key protein of signals triggered by VNS to induce the endogenous CAP [ 28 ]. Ach activates α 7nAChR on macrophages, lymphocytes, and other inflammatory cells, regulating the synthesis and release of inflammatory cytokines and relieving the systemic inflammatory reaction [ 30 ]. The anti-inflammatory effects of taVNS and EA at ST 36 are closely related to the vagus-mediated cholinergic pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 72 In monocytes, α7nAChR activated by non- or strong agonists downregulates NF-κB nuclear translocation and TLR4 expression, and suppresses transcription of pro-inflammatory cytokines. 29 , 36 , 75 De-Pu and colleagues 76 have used nicotine to activate α7nAChR in mice with acute virus-induced myocarditis. The proportion of Th2 and Treg cells increased, and that of Th1 and Th17 cells decreased in the spleen, thus indicating that the α7 subunit is essential for cholinergic suppression of TNF-α and the normal regulation of systemic inflammatory responses.…”
Section: The Role Of the Cholinergic Anti-inflammatory Pathway (Cap) mentioning
confidence: 99%
“…Importantly, the CAP has been shown to decrease the inflammatory response in viral myocarditis. 76 , 86 Activated α7nAChR by nicotine improves the balance of Th1/Th2 and Th17/Treg cell functional axis 76 and significantly down-regulates the expression of TNF-α and IL-6 in mice with CVB3-induced viralmyocarditis. 86 In addition, α7nAChR plays an important role in the expression of ACE-2, the target receptor of SARS-CoV-2.…”
Section: Cap As a Prospective Therapy For Covid-19-related Myocarditimentioning
confidence: 99%